Ethanol gas-sensing characteristic of the Zn2SnO4 nanospheres. Issue 2 (1st February 2016) - An, Dongmin; Mao, Ning; Deng, Guozhi; Zou, Yunling; Li, Yan; Wei, Tong; Lian, Xiaoxue
Abstract: In this paper, Zn2 SnO4 nanospheres were prepared using hexadecyltrimethylammonium bromide (CTAB) and sodium citrate as co-templates. The crystal structure and morphology of as-prepared Zn2 SnO4 product were characterized by X-ray powder diffraction (XRD) and field emission scanning electron microscopy (FE-SEM). A gas sensor was constructed with the prepared Zn2 SnO4 nanospheres and used to detect ethanol gas and some other gases. Because of the special nanostructure and a relative large specific surface area (45.5 m 2 /g), the Zn2 SnO4 -based sensor showed a remarkable gas-sensing performance, including low operating temperature (180 °C), high response (23.4–50 ppm ethanol gas), fast response–recovery time and excellent selectivity to ethanol gas, which suggested the promising application of the Zn2 SnO4 nanomaterials.